2017
DOI: 10.1126/sciadv.1700489
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity of the social brain: Differential change after socio-affective and cognitive mental training

Abstract: Training to understand the feelings and thoughts of others induces structural changes in two divergent social brain networks.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
175
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 221 publications
(187 citation statements)
references
References 111 publications
(255 reference statements)
8
175
0
4
Order By: Relevance
“…In line with the above, the data described in our manuscript using a CFT/CDT of p  < .025 with p  < .05 for family‐wise‐error (FWE) correction (two‐tailed) should have resulted in false‐positive rates no larger than 5%–10%. The applied thresholds furthermore conform to previous research on other (Andrews et al., 2017; Bernhardt et al., 2013; Ecker et al., 2013; Hong et al., 2016) as well as the same data set (Valk et al., 2017), particularly for 20 mm FWHM smoothed surface‐based 2D thickness data where higher smoothing kernels relate to more readily fulfilled assumptions of Gaussian Random Field Theory (Eklund et al., 2016; Flandin & Friston, 2016; Greve & Fischl, 2017). In addition, the effects observed at the above thresholds within the three brain areas of interest are significant for each training cohort separately as evident from post hoc analyses—except for one association at a marginal level of p  = .054.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the above, the data described in our manuscript using a CFT/CDT of p  < .025 with p  < .05 for family‐wise‐error (FWE) correction (two‐tailed) should have resulted in false‐positive rates no larger than 5%–10%. The applied thresholds furthermore conform to previous research on other (Andrews et al., 2017; Bernhardt et al., 2013; Ecker et al., 2013; Hong et al., 2016) as well as the same data set (Valk et al., 2017), particularly for 20 mm FWHM smoothed surface‐based 2D thickness data where higher smoothing kernels relate to more readily fulfilled assumptions of Gaussian Random Field Theory (Eklund et al., 2016; Flandin & Friston, 2016; Greve & Fischl, 2017). In addition, the effects observed at the above thresholds within the three brain areas of interest are significant for each training cohort separately as evident from post hoc analyses—except for one association at a marginal level of p  = .054.…”
Section: Discussionmentioning
confidence: 99%
“…In all models, we controlled for baseline age and sex, given their established effects on brain structure (Salat et al., 2004). Details on structural change as a result of training as such are described elsewhere (Valk et al., 2017).

Behavioral modulation of brain change .

…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI scans, after a 3-month training period, showed that parts of the brain cortex relevant to the trained skill had grown thicker (Valk et al, 2017). Merzenich et al (2014) described degree of plasticity exhibited by sensory circuits.…”
Section: The Accepted Viewmentioning
confidence: 99%
“…However, it is not possible to determine which electron is in which state. The wave function for the state in which both states "a" and "b" are occupied by the electrons can be written (Valk et al, 2017) for an electron:…”
Section: Properties Of An Electronmentioning
confidence: 99%